On the Analogy of Non-Euclidean Geometry of Human Body With Electrical Networks - Alexander Penin; Anatoli Sidorenko; Ashok K Vaseashta (International Journal of Electrical and Computer Engineering (IJECE), 2014)
A review of application of non-Euclidean geometries for interpreting the process of the growth in the human body is presented and features employing non-Euclidean geometries in the electric circuit theory are modeled. Growth of the human body and changes of parameters of an operating regime of an electronic network correspond to projective and conformal transformations which possess an invariant being the cross-ratio of four points. The common mathematical apparatus represents interdisciplinary approach in view of analogy of processes of a different physical nature. The results obtained here demonstrate development of a methodology of application of non-Euclidean geometries and its biological correlation to the growth of human body.DOI:http://dx.doi.org/10.11591/ijece.v4i3.5630